Additive Titanium Manufacturing to Repair Critically Sized Antebrachial Bone Defects in Two Dogs - Janssens, S.D.S.; Willemsen, K.; Magré, J.; Meij, B.P. (VCOT Open, 2023)
Recent developments in the medical field of additive manufacturing (AM) have allowed the creation of patient-specific porous titanium implants for use in the medical field. With correct pore size such scaffolds are able to be integrated into surrounding bone.Two dogs were presented with atrophic non-union of the proximal ulna involving the elbow joint due to previous orthopaedic procedures with severe complications that led to segmental bone defects that were not expected to heal without a secondary intervention. Computed tomography (CT) was performed and porous scaffolds and saw guides were designed in silico and printed by AM. Osteotomies in adjacent healthy bone were guided by patient-specific three-dimensional (3D)-printed nylon saw guides allowing a perfect fit for the 3D-printed implant. In one case the scaffold was filled with bone morphogenic protein and held in place by two plates. In the other case the scaffold was filled with cancellous bone graft and held in place by a titanium plate that was part of the scaffold design. Both cases regained function and weight-bearing without lameness. Osseointegration of the implant was shown in both cases on follow-up CT and radiographs and macroscopically evident in the pores of the 3D implant after plate removal. One dog was euthanatized for unrelated disease and micro-CT revealed solid bone bridging through the inner scaffold tunnel.This study showed the successful application of the design, fabrication and clinical use of a patient-specific 3D-printed titanium implant to repair segmental bone defects of the antebrachium in two dogs.
Keywords: 3D printing; patient-specific implants; non-union; dog